Effectiveness of Competency Leadership Training on Health Systems Performance among Health Management Teams in Selected Healthcare Facilities in Busia County, Kenya. - Osiyel Daniel Edwin; Emma Kabeu; Edna Nyang'echi Nyanchama; Jackson Mulwa; Nancy Wanjiku (Student's Journal of Health Research Africa, 2026)
Background: Healthcare leadership is essential for improving health system performance. This study assessed the effect of competency-based training on healthcare leaders, including both clinical and non-clinical leaders, in Busia County. The intervention focused on strengthening cognitive competency among health managers, particularly younger leaders who required leadership skills development. Methods: An intervention study design was used in Busia County. Eight health facilities were purposively selected, and Health Management Team members were sampled using census sampling. Intervention and control groups were randomly selected from the sampled facilities. Data were collected using a structured interview schedule. The tool was pilot-tested and pre-tested to ensure reliability and validity. Quantitative data were analyzed using the Chi-square test and Fisher’s Exact Test at a significance level of p ≤ 0.05. Results: Gender had no significant influence on health system performance. Age, however, significantly influenced performance, with participants aged 31–40 years performing better than those below 30 years. The intervention led to a significant improvement in performance, with the mean score increasing from 13.31 in the pre-test to 15.58 in the post-test. Competency-based training improved health system performance among healthcare leaders in Busia County. Conclusion: Age influenced performance, while gender did not have a meaningful effect. Health systems should prioritize competency-based leadership training for both clinical and non-clinical managers, with particular attention to younger leaders who may benefit most from structured leadership development.